Os Awaeté e os Toria: associativismo e relações interétnicas na TI Apyterewa - Daniel, Sofia Scanavini (Universidade Federal de São Carlos, 2026)
The Apyterewa Indigenous Land, located in the state of Pará, has been subject to systematic invasions and attacks since the 1980s. Within this context is situated the Parakanã Indigenous people, who self-identify as Awaeté. This study seeks to understand the relational dynamics between the Parakanã and the Associação Indígena Tato’a (AIT), which constitutes the sole representative entity of the people in their relations with the State and partner organizations, and whose team is composed of both Indigenous and non-Indigenous members. The analysis is based on an ethnographic study conducted during the General Assembly of the Parakanã People, which served as a space for meetings among indigenist agencies, partner organizations, the AIT, and the community. In order to examine the internal functioning of the association, an interview was carried out with Tato’a’s technical advisor. Given that the focus of the research lies in the community’s perspectives on the association, semi-structured interviews were also conducted with five Indigenous participants, who articulated their views regarding the association’s work, achievements, and relationships with the non-Indigenous staff employed by the AIT. To apprehend the nuances of each interview, the method of content analysis was employed. Based on the findings of the research, it can be concluded that the relationship between the Indigenous community and the association extends beyond that of a people and the entity that represents or supports them. The AIT has become the voice, organizational form, and locus of resistance of the Parakanã people themselves, managed in accordance with their own interests. The relationship with non-Indigenous individuals working within the AIT is not devoid of criticism, yet it operates both within professional and bureaucratic domains and within the sphere of informal relations, shaped by socio-affective ties.
The Awaeté and the Toria: associativism and interethnic relations in the Apyterewa Indigenous Land
Keywords: TI Apyterewa; Povo Parakanã; Associativismo indígena; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável; 16. Paz, Justiça e Instituições Eficazes